Perceived social support and quality of life in endometrial cancer patients: a longitudinal study - Mandato, Vincenzo Dario; Paterlini, Marcella; Torricelli, Federica; Rabitti, Elisa; Mastrofilippo, Valentina; Aguzzoli, Lorenzo (Frontiers in Oncology, 2024)
Objective This study aimed to assess the influence of medical history, perceived physician-patient communication, and perceived social support on changes in the quality of life (QoL) during the first year of follow-up in patients undergoing surgery for endometrial cancer (EC), the most prevalent gynecological cancer in Western countries, especially in Central and Eastern Europe and North America. Methods This prospective longitudinal study included 98 EC patients. All participants completed the Short Form 36 (SF-36) and the Multidimensional Scale of Perceived Social Support (MSPSS) one month and one year after surgery. Additionally, one month after surgery, they responded to a questionnaire designed by the researchers concerning the key aspects of physician-patient communication. Results Our findings revealed that patients reporting high social support one month after surgery demonstrated significantly improved emotional well-being (EWB) at both one month and one year after the surgery, with statistically significant higher scores in the dimension of EWB (p<0.05). The support from a significant other at one year correlates with greater PF (p<0.005), fewer limitations due to physical health (p<0.05), less pain (p<0.05), less fatigue (p<0.05), and better general and EWB (p<0.05). Conclusion This study underscores the significance of perceived social support for patients cross endometrial cancer. The multifaceted nature of social support, encompassing emotional assistance and information sharing, emerges as a pivotal factor aiding patients in confronting the challenges inherent to EC. This form of support contributes to bolstering psychological well-being and enhancing overall QoL.